Histology and Ultrastructure of the Nephron and Kidney Interstitial Cells in the Atlantic Salmon (Salmo salar Linnaeus 1758) at Different Stages of Life Cycle - Ekaterina A. Flerova; Victoria V. Yurchenko; Alexey A. Morozov; Evgeniy G. Evdokimov; Alena A. Bogdanova; Maksim Yu. Alekseev; Dmitry S. Sendek; Sergey F. Titov (Biology, 2023)
This article presents data on the mesonephros histology and ultrastructure in the Atlantic salmon from the Baltic Sea and Barents Sea populations, with an emphasis on comparisons between the following ontogenetic stages: parr, smolting, adult life at sea, the adults’ return to their natal river to spawn, and spawning. The ultrastructural changes in the renal corpuscle and cells of the proximal tubules of the nephron occurred as early as the smolting stage. Such changes reflect fundamental alterations during the pre-adaptation to life in saltwater. In the Barents Sea population, the adult salmon sampled in the sea had the smallest diameters of the renal corpuscle and proximal and distal tubules, the most narrow urinary space, and the thickest basement membrane. In the group of salmon that entered the mouth of the river and spent less than 24 h in freshwater, the structural rearrangements occurred only in the distal tubules. Better development of the smooth endoplasmic reticulum and a greater abundance of mitochondria in the tubule cells were observed in the adult salmon from the Barents Sea compared to those from the Baltic Sea. Cell-immunity activation was initiated during the parr–smolt transformation. Another pronounced innate-immunity response was registered in the adults returning to the river to spawn.